Attributes affecting passengers' satisfaction of public bus transport service in Kerman, Iran - Khajooei, Ehsan (2012)
Public bus transport is the major mode of transportation in urban areas in Iran since other alternative mode of public transportation such as railways are not extensively developed yet. However, the public bus service has not been able to keep up with the population and travel demand growth. In short, supply has been maintained at the same level, whereas the travel demand has been thriving. Thus, passengers have slowly switched from using the public bus transport services to available and alternative modes of transportation such as mini-vans, taxis and private vehicles. Air pollution and heavy congestion in Kerman is particularly linked with an increased number of vehicles on the road, poorly maintained motorized vehicles and poor strategies for traffic rule enforcement. In addition, bus fares are gradually increased over time to sustain its operation but the public bus transport service level remains poor. In order to attract passengers to use public bus services and leave their private cars or other alternative mode of transportation, the understanding of passengers’ needs and expectations are important. Considering that issues of bus public transport is a localized problem and cannot be cut-and-paste from a successful story of another nation, this research seeks to determine the attributes of passengers’ satisfaction on public bus transport services, specifically in the city of Kerman, Iran. This study employed factor analysis along with one sample T-Test to identify and weigh the importance of each attributes of public bus service quality. The methodology is empirical, where all analyses were based on feedbacks from surveys and interviews conducted on public bus transport users. It was found that public bus transport passengers’ satisfaction comprise of five major criterions which is comfort,reliability, security, accessibility and cost. Overall, the determined needs and expectations of public bus transport users in Kerman, Iran will be useful for corrective measures to improve its performance and service quality and attract more people to use the public bus transport service.